1996
DOI: 10.1073/pnas.93.8.3325
|View full text |Cite
|
Sign up to set email alerts
|

Localization of the central rhythm generator involved in spontaneous consummatory licking in rats: functional ablation and electrical brain stimulation studies.

Abstract: Localization of the central rhythm generator (CRG)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
22
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 32 publications
3
22
0
Order By: Relevance
“…The consistent licking rhythm, which was not affected even by a dose (20 mg/kg) high enough to induce stereotypic licking, suggests that cocaine did not exert any apparent effects on brain stem mechanisms controlling licking rhythm (Wiesenfeld et al, 1977;Brozek et al, 1996;Travers et al, 1997). Nonetheless, our observed trend (though not significant) toward fewer long periods and more short periods within bursts is in the same direction as Knowler and Ukena (1973) observed at low doses in their sample of three rats.…”
Section: Discussionsupporting
confidence: 41%
“…The consistent licking rhythm, which was not affected even by a dose (20 mg/kg) high enough to induce stereotypic licking, suggests that cocaine did not exert any apparent effects on brain stem mechanisms controlling licking rhythm (Wiesenfeld et al, 1977;Brozek et al, 1996;Travers et al, 1997). Nonetheless, our observed trend (though not significant) toward fewer long periods and more short periods within bursts is in the same direction as Knowler and Ukena (1973) observed at low doses in their sample of three rats.…”
Section: Discussionsupporting
confidence: 41%
“…To test the hypothesis that NPY may act in concert with norepinephrine (NE), we examined neurons showing suppressed responses in the presence of a Y2 agonist and demonstrated a greater degree of suppression to a Y2 agonist/NE cocktail. These suppressive effects on preoromotoneurons may reflect a satiety pathway originating from A2 neurons in the caudal brain stem.oromotor; ingestion; reticular formation; norepinephrine CIRCUITS CONTROLLING THE CONSUMMATORY behaviors of ingestion are located in the lower brain stem (7,38,40,56). These circuits extend from the pons to the spinal medullary junction to encompass both sensory and motor nuclei, as well as specific regions of the reticular formation (RF).…”
mentioning
confidence: 99%
“…oromotor; ingestion; reticular formation; norepinephrine CIRCUITS CONTROLLING THE CONSUMMATORY behaviors of ingestion are located in the lower brain stem (7,38,40,56). These circuits extend from the pons to the spinal medullary junction to encompass both sensory and motor nuclei, as well as specific regions of the reticular formation (RF).…”
mentioning
confidence: 99%
“…Based on evidence from acute animal studies, investigators have suggested that licking and chewing (and other oral rhythmic behaviors) share a common CTN (Carvalho & Gerstner, 2004;Gerstner & Goldberg, 1991;Goldberg & Chandler, 1990). Evidence exists that the licking CTN is located at the same site as the masticatory CTN (Brozek et al, 1996). The concept of a shared CTN probably does not conflict with the more recent model presented by Lund and Kolta describing how CPG circuitry could be modified to produce distinct chewing forms (Lund & Kolta, 2006); at issue is whether the modifiable masticatory CPG output of the Lund-Kolta model in fact produces the licking "form".…”
Section: Licking and Sucklingmentioning
confidence: 99%